2012
DOI: 10.1039/c2cp23756c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the thermal isomerisation pathways in an asymmetric double azobenzene switch

Abstract: Here we report a photochemical and kinetic study of the thermal relaxation reaction of a double azobenzene system, in which two azobenzene photochromic units are connected via a phenyl ring. Upon UV irradiation, three thermally unstable isomers are formed. Kinetic studies using arrayed (1)H-NMR spectroscopy revealed four distinct barriers for the thermal reversion to the stable isomer. The double isomerised Z,Z-2 can revert thermally to the E,E-2 isomer via either of two isomerisation pathways. The thermal Z t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 60 publications
0
45
0
2
Order By: Relevance
“…For the herein‐discussed electronically neutral azobenzenes, an inversion mechanism is commonly accepted 16a. 22 An isokinetic plot24 (Δ H ≠ versus Δ S ≠ ) as well as an Exner plot25 (log k 39 °C versus log k 67 °C ) supported this assumption and demonstrated that the mechanism is equal for all examples 3 – 9 (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 77%
“…For the herein‐discussed electronically neutral azobenzenes, an inversion mechanism is commonly accepted 16a. 22 An isokinetic plot24 (Δ H ≠ versus Δ S ≠ ) as well as an Exner plot25 (log k 39 °C versus log k 67 °C ) supported this assumption and demonstrated that the mechanism is equal for all examples 3 – 9 (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 77%
“…The long τ 1/2 indicates high Δ E a for per metastable Z-AZO on RGO 13 . As shown in Table 1 , Δ E a for Z- ortho -AZO on RGO up to 1.2 eV calculated by equation (2) substantially outperforms other AZO derivatives 5 7 8 9 10 29 and noticeably conquers the limitation of short reversion of Z-AZO. Where T is the storage temperature and τ 1/2 is the half-life.…”
Section: Discussionmentioning
confidence: 84%
“…[16a,22] Ein isokinetischer Plot [24] (DH°gegen DS°)u nd ein Exner-Plot [25] (log k 39 8 8C gegen log k 67 8 8C )s tützten diese Annahme und zeigten, dass der vorliegende Mechanismus für alle Beispiele 3-9 identisch ist (siehe die Hintergrundinformationen). Für die hier untersuchten elektronisch neutralen Azobenzole ist ein Inversionsmechanismus allgemein akzeptiert.…”
Section: Methodsunclassified
“…[*] L. Schweighauser [23] 22] Ein isokinetischer Plot [24] (DH°gegen DS°)u nd ein Exner-Plot [25] (log k 39 8 8C gegen log k 67 8 8C )s tützten diese Annahme und zeigten, dass der vorliegende Mechanismus für alle Beispiele 3-9 identisch ist (siehe die Hintergrundinformationen).…”
Section: Die Zunahme Der Sterischen Hinderung Mit Der Grçße Vonunclassified